Monoallelic mutations in the translation initiation codon of KLHL24 cause skin fragility - He, Yinghong; Maier, Kristin; Leppert, Juna; Haußer-Siller, Ingrid; Schwieger-Briel, Agnes; Weibel, Lisa; Theiler, Martin; Kiritsi, Dimitra; Busch, Hauke; Boerries, Melanie; Hannula-Jouppi, Katariina; Heikkilä, Hannele; et al. (The American journal of human genetics, 2016)
The genetic basis of epidermolysis bullosa, a group of genetic disorders characterized by the mechanically induced formation of skin blisters, is largely known, but a number of cases still remain genetically unsolved. Here, we used whole-exome and targeted sequencing to identify monoallelic mutations, c.1A>G and c.2T>C, in the translation initiation codon of the gene encoding kelch-like protein 24 (KLHL24) in 14 individuals with a distinct skin-fragility phenotype and skin cleavage within basal keratinocytes. Remarkably, mutation c.1A>G occurred de novo and was recurrent in families originating from different countries. The striking similarities of the clinical features of the affected individuals point to a unique and very specific pathomechanism. We showed that mutations in the translation initiation codon of KLHL24 lead to the usage of a downstream translation initiation site with the same reading frame and formation of a truncated polypeptide. The pathobiology was examined in keratinocytes and fibroblasts of the affected individuals and via expression of mutant KLHL24, and we found mutant KLHL24 to be associated with abnormalities of intermediate filaments in keratinocytes and fibroblasts. In particular, KLHL24 mutations were associated with irregular and fragmented keratin 14. Recombinant overexpression of normal KLHL24 promoted keratin 14 degradation, whereas mutant KLHL24 showed less activity than the normal molecule. These findings identify KLHL24 mutations as a cause of skin fragility and identify a role for KLHL24 in maintaining the balance between intermediate filament stability and degradation required for skin integrity.
Gesehen am 07.05.2020